Delamination of lithospheric mantle evidenced by Cenozoic potassic rocks in Yunnan, SW China: A contribution to uplift of the Eastern Tibetan Plateau - Chen, B.; Long, X.; Wilde, Simon; Yuan, C.; Wang, Q.; Xia, X.; Zhang, Z. (Elsevier BV, 2017)
© 2017 Elsevier B.V. New zircon U–Pb ages, mineral chemical data, whole-rock geochemistry and Sr–Nd isotopes from the potassium-rich intrusions in the Yunnan area, SW China, were determined to provide constraints on the uplift of the Eastern Tibetan Plateau. The intrusive rocks consist of shoshonitic syenites (high-Mg syenites, low-Mg syenites and syenite porphyries) and potassic granitoids (granite porphyries). Zircon LA-ICP-MS U–Pb dating indicates coeval emplacement ages of ~ 35 Ma. The shoshonitic syenites have alkaline affinities and the enrichment in LILEs and LREEs (e.g. La, Sr, U, Pb), with depletion of HFSEs (e.g. Nb, Ti, Ta) and weak Eu anomalies. They display uniform Sr–Nd–Lu–Hf isotopic compositions with similar initial 87 Sr/ 86 Sr ratios (0.7073–0.7079), enriched e Nd (t) values (- 6.8 to - 4.3) and mostly negative zircon e Hf (t) values ranging from - 4.6 to + 0.1. The high-Mg syenites have high MgO, Fe 2 O 3 T , TiO 2 , CaO, Cr, Ni concentrations and relatively high Mg # (60–68), indicating an origin from enriched lithospheric mantle. The low-Mg syenites and syenite porphyries are geochemically distinct with the high-Mg syenites, but the insignificant variations in major elements, linear trends of La against (La/Yb) N and similar Sr–Nd isotopic compositions to the high-Mg syenites suggest that they were produced by different degrees of partial melting of the same enriched mantle source. The potassic granitic intrusions are sub-alkaline with a strongly peraluminous character. They display an S-type granite affinity, with high Al 2 O 3 /TiO 2 and low CaO/Na 2 O and K 2 O/Al 2 O 3 ratios, suggesting a pelitic source. They are LREE-enriched and have relatively flat HREE patterns with weakly negative Eu anomalies and positive Rb, U, and Pb anomalies and negative Nb, Ta, and Ti anomalies. They have relatively high initial 87 Sr/ 86 Sr ratios (0.7143) and enriched Nd isotopic compositions [ e Nd (t) = - 4.1]. Their zircon e Hf (t) values (- 4.0 to + 0.09) and old two-stage Hf model ages (T DM c  = 1.16–1.36 Ga) suggest that they were generated by partial melting of an ancient K-rich crust. The petrogenesis of the potassic intrusive rocks with their uniform Nd model ages (T DM  = 968–1168 Ma) indicates that the lithospheric mantle beneath Yunnan was enriched by metasomatism related to ancient oceanic subduction. Considering the widespread and coeval nature of potassium-rich rocks in Eastern Tibet, we consider that delamination of metasomatized lithospheric mantle beneath Yunnan in the Eocene was a result of the India–Asia collision, which triggered partial melting of both the lithospheric mantle and the K-rich crust, and contributes to uplift of the Eastern Tibetan Plateau.